2007
DOI: 10.1016/j.gene.2007.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of coastal bottlenose dolphins revealed by structurally and functionally diverse hemoglobins

Abstract: Studies of structure-function relationships in the respiratory proteins of marine mammals revealed unexpected variations in the number and types of hemoglobins (Hbs) present in coastal bottlenose dolphins, Tursiops truncatus. We obtained blood samples from free-ranging coastal bottlenose dolphins as a component of capture-release studies. We found that the oxygen-binding functions of bottlenose dolphin blood are poised between effector-saturated and unsaturated levels, enabling exercise-dependent shifts in oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…A sampling of 27 coastal bottlenose dolphins (Turiops truncatus) exhibited different Hb oxidation rates (Remington et al, 2007). This was attributed to the observation that some dolphins had Hb isoforms that differed compared to the other dolphins examined.…”
Section: Autooxidation Of Different Hbsmentioning
confidence: 99%
“…A sampling of 27 coastal bottlenose dolphins (Turiops truncatus) exhibited different Hb oxidation rates (Remington et al, 2007). This was attributed to the observation that some dolphins had Hb isoforms that differed compared to the other dolphins examined.…”
Section: Autooxidation Of Different Hbsmentioning
confidence: 99%
“…Although a few cetacean α- and β-globins have been sequenced so far and analyzed functionally ( Brix et al 1990 ; Tellone et al 2000 ; Corda et al 2003 ; Remington et al 2007 ; Manconi et al 2009 ), no previous work has characterized the α- and β-globins clusters on this particular lineage. Most of the earlier studies have shown that the oxygen-binding behavior of cetaceans’ hemoglobin has unusual properties probably linked to their peculiar diving behavior: lower intrinsic oxygen affinities and greater Bohr effects.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics could enhance oxygen release to respiring tissues when exercise causes a drop in levels of ATP. Remington et al (2007) highlighted that the relative low-oxygen affinities are intrinsic to the Hb’s structure and showed that genetic diversity was clearly responsible for the variations in Hb type and function of these animals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential for long‐distance dispersal within T. truncatus , significant population structure over relatively small geographic distances have been detected among coastal regional populations such as those found along the coasts of the Gulf of Mexico, Florida, Bahamas, New Zealand, United Kingdom, Mediterranean and Black Seas (Wells, ; Hoelzel et al ., ; Parsons et al ., ; Torres et al ., ; Natoli et al ., , ; Sellas et al ., ; Parsons et al ., ; Remington et al ., ; Viaud‐Martínez et al ., ; Tezanos‐Pinto et al ., ; Urian et al ., ). The only T. truncatus population studied to date, where no significant population structure was found is in the North Atlantic off the Azores and Madeira (Quérouil et al ., ).…”
Section: Introductionmentioning
confidence: 99%